Who is the victim? The effect of medical errors on physicians and patients (2009)
Medical error is an adverse event that could be prevented, given the current state of medical knowledge. It has been defined as the failure of a planned action to be completed as intended or the use of a wrong plan to achieve an aim. Medical errors can occur in any health care setting in the form of an ‘adverse drug event, improper transfusion, surgical injuries and wrong site injuries, suicide, restraint-related injury or death, falls, burn, pressure ulcers and mistaken patient identity, When errors occur, ethics, professional policy and the law suggest that timely and candid disclosure be the standard practice. Disclosure however raises a number of ethical, legal, and psychological issues which will be discussed in this study. The study further examines the philosophical basis for disclosure and non-disclosure; the duty owed by the physician to the patient; the effect of disclosure on patients and physicians. In discussing the effect of medical error on patients and physicians, the benefit and harm of disclosure and its effect on patient/physician relationship will be examined